L’Afrique sub-saharienne face aux famines énergétiques - Géraud Magrin (EchoGéo)
The low consumption of energy is a cause and a symptom of Africa underdevelopment. The fuel shortage which threatens the world seems to induce two different paths. The oil-producing countries have to avoid the traps of the "commodities curse"; they have to use the oil incomes to strengthen both their State and their economy. The other countries have to think of the after oil. Everywhere innovations have to be sought so that economy be no more an hindrance, but a development catalyst.